Pelatihan Seni bagi Kelompok Gejog Lesung Surontoko untuk Mendukung Program Rintisan Desa Budaya Kalurahan Argomulyo Yogyakarta - Hana Permata Heldisari; Nur Arif Anandhita (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to improve the competence of the Gejog Lesung Surontoko group through art training to support the Argomulyo Village cultural village pilot program. The method of implementing the service activity uses discussions, demonstrations, imitations, and drills. Data of this activity are collected using observation, interviews, and focus group discussion and are analyzed interactively. The results of this service activity show that members of the Gejog Lesung Surontokan art group have skills and insight in arranging songs in the form of rhythmic variations and voice harmonization by singers. In addition, a video work has been produced which can be used as a portfolio for managing cultural master numbers.